The "realist search": A systematic scoping review of current practice and reporting. (15th December 2019) - Booth, Andrew; Briscoe, Simon; Wright, Judy M.
Abstract : The requirement for literature searches that identify studies for inclusion in systematic reviews should be systematic, explicit, and reproducible extends, at least by implication, to other types of literature review. However, realist reviews commonly require literature searches that challenge systematic reporting; searches are iterative and involve multiple search strategies and approaches. Notwithstanding these challenges, reporting of the "realist search" can be structured to be transparent and to facilitate identification of innovative retrieval practices. Our six‐component search framework consolidates and extends the structure advanced by Pawson, one of the originators of realist review: formulating the question, conducting the background search, searching for program theory, searching for empirical studies, searching to refine program theory and identifying relevant mid‐range theory, and documenting and reporting the search process. This study reviews reports of search methods in 34 realist reviews published within the calendar year of 2016. Data from all eligible reviews were extracted from the search framework. Realist search reports poorly differentiate between the different search components. Review teams often conduct a single "big bang" multipurpose search to fulfill multiple functions within the review. However, it is acknowledged that realist searches are likely to be iterative and responsive to emergent data. Overall, the search for empirical studies appears most comprehensive in conduct and reporting detail. In contrast, searches to identify and refine program theory are poorly conducted, if at all, and poorly reported. Use of this framework offers greater transparency in conduct and reporting while preserving flexibility and methodological innovation.